ENHANCING EFL LEARNING THROUGH PODCAST AUDIO-ASSISTED LISTENING - Gunawan, Muhammad Handi; Damayanti, Hemalia; Hanifa, Eisha Sabila Dieni; Gunawan, Aninda Putri; Suherdi, Didi (Indonesian EFL Journal, 2023)
This study investigates students’ experience in using podcasts to support their learning in the classroom. This research involves 18 private senior high school students in West Java province. There are three instruments used in this study. Classroom observations from recorded videos are used to capture the listening activities conducted in the classroom and students’ responses. Students' opinions on the usage of podcasts are collected through a questionnaire that includes closed-ended questions with dichotomous (Yes/No) questions and elaborated answers on the choices. The interview session exposes the students' reactions to the podcast application, which aids students' listening skills. The study results show that students can use podcasts to scaffold their language-learning listening experiences. Furthermore, students find that listening to podcasts helps them focus and explore various intriguing topics.Keyword: Podcast; listening comprehension; listening skill.